The degree to which third-grade teachers practice McCarthy model in Math teaching (Journal of Hama University, 2025)
The aim of the research is to investigate the degree to which third-grade teachers practice the McCarthy-format model in Math teaching, and to know the differences in their viewpoints, the degree to which they practice this model, according to the two variables (years of experience and number of training courses), where the descriptive analytical approach was used, and a questionnaire was designed consisting of (28) items, and were applied during the first semester of the school year 2023-2024, on a sample of (164) male and female teachers distributed in the schools of the first cycle of basic education in the city of Tartous The results of the study showed:The degree of third-grade teachers' practice of the McCarthy-format model in Math teaching came to a good rate.- There are no statistically significant differences between the average teachers' scores according to the variable number of years of experience.- There are no statistically significant differences between the average scores of teachers according to the variable of training courses.
Keywords: McCarthy's formic model, degree, practice, third grade teachers